2016
DOI: 10.1016/j.simyco.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Hidden diversity in Thyridaria and a new circumscription of the Thyridariaceae

Abstract: A multigene analysis of a combined ITS-LSU-SSU-rpb2-tef1 sequence data matrix was applied to infer the phylogenetic position of the genus Thyridaria in the Pleosporales. The generic type of Thyridaria, T. broussonetiae (syn. T. incrustans), is situated in a clade currently named Roussoellaceae, which becomes a synonym of Thyridariaceae. However, Thyridaria rubronotata does not belong to this clade, but is here recognised as Cyclothyriella rubronotata in its own family Cyclothyriellaceae. The Thyridariaceae con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 47 publications
2
74
0
Order By: Relevance
“…Although the phylogenetic placement of the type species of Monodictys , M. putredinis , remains unclear, this species was reported as the asexual morph of Ohleria brasilensis (Samuels 1980). Ohleria was recently included in the Ohleriaceae, Pleosporales (Jaklitsch & Voglmayr 2016), which is distant from the M. capensis clade. Our results agree with the phylogeny presented by Tanaka et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the phylogenetic placement of the type species of Monodictys , M. putredinis , remains unclear, this species was reported as the asexual morph of Ohleria brasilensis (Samuels 1980). Ohleria was recently included in the Ohleriaceae, Pleosporales (Jaklitsch & Voglmayr 2016), which is distant from the M. capensis clade. Our results agree with the phylogeny presented by Tanaka et al.…”
Section: Resultsmentioning
confidence: 99%
“…Although molecular data for the type species of Monodictys are not available, based on culture methods, M. putredinis has been reported as the asexual morph of Ohleria brasiliensis (Samuels 1980). Recently, Ohleria was included in the pleosporalean family Ohleriaceae (Jaklitsch & Voglmayr 2016). Phylogenetic reassessment of species in Monodictys and related sexual genera, including types, is needed to clarify the taxonomy of this genus.…”
Section: Taxonomymentioning
confidence: 99%
“…Pleosporalean species are characterised by pseudothecial ascomata usually with a papilla and a peridium composed of several layers of cells (Zhang et al 2009, 2012, Hyde et al 2013, Jaklitsch and Voglmayr 2016, Jaklitsch et al 2017). Asci are bitunicate, usually fissitunicate and produced within a persistent hamathecium with or without pseudoparaphyses (Ariyawansa et al 2013, 2014, 2015, Hyde et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Asci are bitunicate, usually fissitunicate and produced within a persistent hamathecium with or without pseudoparaphyses (Ariyawansa et al 2013, 2014, 2015, Hyde et al 2013). Ascospores are generally septate but vary in colour and shape, with or without a gelatinous sheath (Zhang et al 2009, 2012, Hyde et al 2013, Jaklitsch and Voglmayr 2016, Jaklitsch et al 2017). Asexual morphs can be coelomycetous or hyphomycetous (Zhang et al 2009, 2012, Hyde et al 2013, Ariyawansa et al 2014, 2015, Hernández-Restrepo et al 2017, Valenzuela-Lopez et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…(6)(7)(8)(9)(10)(11)(12)(13); and various species of Exophiala (Chaetothyriales) (14). Two further poorly sporulating or nonsporulating dematiaceous fungi, Rhytidhysteron rufulum (Hysteriales) and Parathyridaria (previously Roussoella) percutanea (Thyridariaceae), have also recently been described from subcutaneous mycetoma-like infections in humans, although grain and sinus tract formation has not been reported to date (15)(16)(17)(18)(19). Since a number of recent studies have reported significant species-specific differences in antifungal susceptibility (13,(20)(21)(22)(23), the accurate identification of the causative agents of eumycetoma and related subcutaneous phaeohyphomycoses is likely to be paramount in directing appropriate antifungal interventions.…”
mentioning
confidence: 99%